2017
DOI: 10.18203/2319-2003.ijbcp20174799
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ipomoea aquatica Forsk. in cyclophosphamide induced dyslipidaemia in albino rats

Abstract: Background: Cyclophosphamide (CP) is commonly used as anticancer and immuno suppressant agent. It induces hyperlipidemia and myocardium damage. Ipomoea aquatic Forsk. is traditionally used for cardiovascular disease, paralysis and general debility. The present study was done to evaluate the protective effect of the plant against CP induced dyslipidaemia in albino rats.Methods: Twenty albino rats were divided into 4 groups of 5 animals each. Group I (normal group) received normal saline intraperitoneally. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…One of the key findings of the current investigation was that CYCP elicited significant disruption of lipid homeostasis characterized by up-regulation in the mean concentrations of erythrocyte cholesterol, triacylglycerol, phospholipids, non-esterified fatty, and cholesterol-phospholipids molar ratio. This observation is characteristic changes that have been reported during xenobiotics, including CYCP administration [ [64] , [65] , [66] , [67] ].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…One of the key findings of the current investigation was that CYCP elicited significant disruption of lipid homeostasis characterized by up-regulation in the mean concentrations of erythrocyte cholesterol, triacylglycerol, phospholipids, non-esterified fatty, and cholesterol-phospholipids molar ratio. This observation is characteristic changes that have been reported during xenobiotics, including CYCP administration [ [64] , [65] , [66] , [67] ].…”
Section: Discussionsupporting
confidence: 53%
“…The observed CYCP-induced hypertriacylglycerolemia in this study could result from either increased VLDL production or decreased VLDL clearance [ 68 ]. Increased cholesterol is equally associated with increased cholesterol anabolism and/or decreased cholesterol catabolism [ 65 ]. The current research demonstrated a CYCP-induced significant increase in phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Senthilkumar et al [5] reported that treatment of rats with 150 mg/kg of CPA for 2 days caused a significant alterations in serum cholesterol and none significant changes were observed in serum triglycerides. CP administration significantly (P<0.05) increased the levels of triglyceride, total cholesterol, LDL-cholesterol and decreased the level of HDL-cholesterol in toxic group compared to normal group [4]. 5-FU is widely used in the treatment of a range of cancers, including colorectal and breast cancers, and cancers of the aerodigestive tract.…”
Section: Introductionmentioning
confidence: 97%
“…Cyclophosphamide (CP) is commonly used as anticancer and immuno suppressant agent. It is mainly used for ovarian cancer, breast cancer, chronic lymphocytic leukemia, non-Hodgkin's lymphoma, neuroblastoma, soft tissue sarcoma, rhabdomyosarcoma, Wilms' tumor, and immunosuppressant agent [3,4]. It induces hyperlipidemia and myocardium damage [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation